Strategi Penguatan Sektor Peternakan dalam Swasembada Pangan Nasional melalui Rantai Pasok, Korporatisasi Peternak, dan Pemasaran Mikro - Noni N. Neno (BISMA : Business and Management Journal, 2026)
National food self-sufficiency is determined not only by the availability of staple foods but also by the capacity to provide animal-source foods that are safe, nutritious, affordable, stable, and sustainable. However, smallholder livestock systems continue to face major constraints, including weak supply chains, low bargaining power of farmers, limited business institutions, and underdeveloped value-added marketing. This study aims to analyze strategies for strengthening the livestock sector in supporting national food self-sufficiency through the integration of supply chain management, farmer corporatization, and micro-marketing. The study employed a narrative literature review using a descriptive-qualitative approach and thematic synthesis of 41 selected sources from scientific databases and official policy documents. The findings indicate that strengthening the livestock sector requires integrated input aggregation, production recording, quality standardization, cooperative-based business governance, fair market contracts, product processing, packaging improvement, digital promotion, social commerce utilization, and local market partnerships. The study concludes that the synergy of these three strategies can improve business efficiency, strengthen farmers’ competitiveness and bargaining position, and create a more sustainable livestock system. The practical implication is the need to develop area-based livestock strengthening models as a reference for governments, cooperatives, and business actors in supporting national food self-sufficiency.